TINJAUAN APLIKASI GREEN DESIGN PADA INTERIOR CAFÉ BOUNDARY DI BANDUNG DENGAN KONSEP HOMEY - Lodhita, Fellicia; Darmayanti, Tessa Eka (Universitas Medan Area, 2024)
Increasing global warming has a negative impact on the earth and its contents. The real manifestation of the failure of the global development model can be seen from the uncertain climate change in Indonesia. This inconvenience affects people's productivity due to air quality and air pollution. Bandung is the 4th largest city in Indonesia with a significant population growth, therefore Bandung is an attraction for developing businesses. So that the application of green design in cafes is the right answer and of course can increase the efficiency and effectiveness of energy use and the resources needed. Cafe Boundary presents a green design that carries a homey concept. The concept of a design is important because it involves actions to be taken in the future, and it was found that this cafe responds to nature and is expected to give a sense of calm, peace and coolness in the space. Through this design, a Boundary cafe is produced with a natural interior that can answer sustainable business ideas supported by the application of green design in it. The purpose of this study was to determine the impact of green design on a cafe in Bandung and to support the application of the homey concept to this cafe. Data collection was carried out using qualitative methods with observation, interviews and documentation. Through this study it is hoped that it can develop readers' insights regarding the application of green design to an interior design, especially cafes and perspectives to improve the quality of life by applying green design.